PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL NOMOR HEADS TOGETHER (NHT) TERHADAP HASIL BELAJAR SISWA KELAS VII SMPN 13 PEKANBARU (Proceeding 7th International Seminar on Regional Education, 2015)
AbstractThis research is an experimental study conducted to determine the effect oftheimplementation ofcooperative learning model structural approach Number HeadTogether (NHT) format hematics learning outcomes of students. The designof thisresearch was aquasi experimental. The population inthis research were class VIISMPN 13 Pekanbaru. With purposive sampling technique was taken two classes ofthe population VII.5 class (class conventional) and VII.7 (experimental class)toserve as the research sample. Based on theresults oftests of homogeneity of thefinal data obtained and the valuesobtained So it canbe said that the two groups ofsamples have the same variance (homogeneous). Mean while, based onthe resultsofthe t-test values obtained rightside and = 1.67withvalue dk= 69 and , to obtain thenrejected, or it canbe said that the mathematic learning outcomes of students inexperimental classe sare better thanthe control class. Further, the calculationresult of the influence coefficients (Kp) was Kp=4.3%In other words, it can beconcluded that the effect ofthe application of cooperative learning modelNumber Head Together (NHT) structural approach to improving student learningoutcomes was 4.3%.Key Word : Effect, NHT, mathematic learning outcomes